THE ROLE OF DIGITAL TRANSFORMATION STRATEGY CAPABILITIES IN KNOWLEDGE LEADERSHIP AT IRAQI UNIVERSITIES - Asst. Prof. Dr. Hatem Ali Abdullah; Zaidoun Farid Ahmed (Scholar Express Journals, 2024)
This study aims to identify the role of Digital Transformation Strategy (DTS) capabilities (i.e., administrative and operational) in Knowledge Leadership (KL) with its dimensions (i.e., leadership skills, collaboration and trust, knowledge integration, and creativity) at Iraqi universities. The researchers resorted to this study to check the extent of the presence of digital transformation strategy and knowledge leadership in the Middle East, especially in developing countries including Iraq. This study adopted a descriptive-analytical approach in data collection. It demonstrates a survey based on the Likert scale; data analysis was performed using SPSS software. The survey was distributed to a random sample of 285 teaching staff to represent the original population of teaching staff at the Northern Technical University (NTU). Results showed that digital transformation strategy has a significant impact on knowledge leadership practices at the Northern Technical University. It also revealed that operational capabilities have the most influence on knowledge leadership practices, and it provides a framework for understanding how digital transformation strategy is adopted, especially at the Northern Technical University and generally in Iraqi universities. Therefore, this study is considered unique and important in the Iraqi educational environment, and its results can be generalized to other Iraqi universities, as they are culturally, technologically, and administratively similar
Keywords: Digital Transformation Strategy; DTS; higher education; Iraq; knowledge leadership KL